2019
DOI: 10.1021/acsami.9b01242
|View full text |Cite
|
Sign up to set email alerts
|

High-Throughput Equilibrium Analysis of Active Materials for Solar Thermochemical Ammonia Synthesis

Abstract: Solar thermochemical ammonia (NH3) synthesis (STAS) is a potential route to produce NH3 from air, water, and concentrated sunlight. This process involves the chemical looping of an active redox pair that cycles between a metal nitride and its complementary metal oxide to yield NH3. To identify promising candidates for STAS cycles, we performed a high-throughput thermodynamic screening of 1,148 metal nitride/metal oxide pairs. This data-driven screening was based on Gibbs energies of crystalline metal oxides an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 37 publications
0
33
0
Order By: Relevance
“…[18,25,[61][62][63] We previously applied a thermodynamic screening approach based on the descriptor G δ (T) to rapidly identify active materials for solarthermal ammonia synthesis in which ~1,100 oxide and nitride pairs were analyzed. [7] Here, we demonstrate that this approach can be applied to any CL process that operates at or near equilibrium conditions with temperatures up to at least 1800 K, irrespective of the active material class (e.g. oxide, halide, etc.…”
Section: Introductionmentioning
confidence: 88%
See 2 more Smart Citations
“…[18,25,[61][62][63] We previously applied a thermodynamic screening approach based on the descriptor G δ (T) to rapidly identify active materials for solarthermal ammonia synthesis in which ~1,100 oxide and nitride pairs were analyzed. [7] Here, we demonstrate that this approach can be applied to any CL process that operates at or near equilibrium conditions with temperatures up to at least 1800 K, irrespective of the active material class (e.g. oxide, halide, etc.…”
Section: Introductionmentioning
confidence: 88%
“…Chemical looping processes are a promising route for improving energy efficiency, [1][2][3][4] leveraging renewable energy sources, [5][6][7][8][9][10][11] facilitating chemical conversions, [12][13][14][15][16][17][18][19][20] and reducing undesirable emissions across many sectors of the chemical industry. [21][22][23][24][25][26] In a chemical looping (CL) process, the overall reaction is separated into multiple (typically two) subreactions, each mediated by the redox chemistry of a "looped" active material.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Particularly for ΔSsolid of the CeO2/CeO2-δ redox pair (δ=0.03), it was demonstrated that the relative differences between calculated and measured values are below 12%, although it is found in references [20,23] that this method might over-estimate ΔSsolid. Regarding ΔHsolid of pure and Sm-doped ceria pairs (δ=0.03), the relative differences are also below 12%, demonstrating sufficient accuracy of this method which is expected to be more efficient enabled by the advancement and power of highthroughput computational tools [15][16] . a Entropy and enthalpy units are J (0.5 mol O2) -1 K -1 and kJ (0.5 mol O2) -1 ; b Obtained from measured reduction entropy minus 0.5SO2…”
Section: Colourful Figure Is Available On Website 2 First-principles Predictions Of Descriptorsmentioning
confidence: 93%
“…Although considerable materials [4] have been examined including ceria [5][6][7][8] , ferrites [9][10][11] and perovskites [12][13][14] , the state-of-the-art solar-to-chemical energy conversion efficiency was as low as ~5% for solar thermochemical CO2 splitting [5] . Therefore, computational assessments of materials are still of great importance [15][16][17] . Intuitively, the thermodynamically suitable redox materials can be identified based on the fundamental concept that the change in the Gibbs free energy, ΔG, should be negative for the two cycle steps (reactions 2 and 3).…”
mentioning
confidence: 99%